2010
DOI: 10.1152/ajpendo.00132.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of atorvastatin on the regeneration of pancreatic β-cells after streptozotocin treatment in the neonatal rodent

Abstract: Marchand KC, Arany EJ, Hill DJ. Effects of atorvastatin on the regeneration of pancreatic ␤-cells after streptozotocin treatment in the neonatal rodent. Am J Physiol Endocrinol Metab 299: E92-E100, 2010. First published April 13, 2010; doi:10.1152/ajpendo.00132.2010.-To investigate the role of statins in ␤-cell regeneration a model of streptozotocin (STZ)-induced ␤-cell injury was used in the neonatal rat. We hypothesized that ␤-cell growth and regeneration would increase following treatment with atorvastatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…We and others have shown that young rodents retain the capacity to partially regenerate β-cell mass after STZ ablation, but this regenerative potential is mitigated in adulthood (Bonner-Weir et al 1981, Portha et al 1989, Wang et al 1996, Thyssen et al 2006, Tschen et al 2009, Chamson-Reig et al 2010, Cox et al 2010, Marchand et al 2010, Nicholson et al 2010. This loss of regenerative capacity coincides with the decline seen here in both Ins + Glut2 LO cell abundance, and a change in their anatomical location.…”
Section: :3supporting
confidence: 59%
“…We and others have shown that young rodents retain the capacity to partially regenerate β-cell mass after STZ ablation, but this regenerative potential is mitigated in adulthood (Bonner-Weir et al 1981, Portha et al 1989, Wang et al 1996, Thyssen et al 2006, Tschen et al 2009, Chamson-Reig et al 2010, Cox et al 2010, Marchand et al 2010, Nicholson et al 2010. This loss of regenerative capacity coincides with the decline seen here in both Ins + Glut2 LO cell abundance, and a change in their anatomical location.…”
Section: :3supporting
confidence: 59%
“…Endothelium function may therefore be improved. Atorvastatin was reported to improve the regeneration of β-cell mass due to increase of intro-islet endothelial cells [8]. …”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, recent studies showed that beneficial effect of atorvastatin on insulin resistance were due to decrease of inflammation [7]. On the other hand, functional β-cell mass was expanded with atorvastatin in the neonatal rodent [8]. However, whether the β-cell function will be affected is a concern.…”
Section: Introductionmentioning
confidence: 99%
“…After 8 weeks of treatment, an oral glucose tolerance test (OGTT) was performed under short ether narcosis. Blood glucose and plasma insulin were measured after overnight fasting and 120 minutes after an oral glucose load of 0.3 g/100 g body weight given through a gauge (15,16 …”
Section: Animalsmentioning
confidence: 99%